Paclitaxel with Cisplatin as Salvage Treatment for Patients with Previously Treated Advanced Transitional Cell Carcinoma of the Urothelial Tract - Ji Eun Uhm; Ho Yeong Lim; Won Seog Kim; Han Yong Choi; Hyun Moo Lee; Byeong-Bae Park; Keunchil Park; Won Ki Kang (Neoplasia: An International Journal for Oncology Research, 2007)
BACKGROUND: This study was performed to evaluate the safety and efficacy of paclitaxel with cisplatin as salvage therapy in patients previously treated with gemcitabine and cisplatin (G/C) for advanced transitional cell carcinoma (TCC) of the urothelial tract. METHODS: Twenty-eight patients with metastatic or locally advanced TCC who had received prior G/C chemotherapy were enrolled. All patients received paclitaxel (175 mg/m2) and cisplatin (60 mg/m2) every 3 weeks for eight cycles or until disease progression. RESULTS: The median age was 61 years (range, 43–83 years), and the median Eastern Cooperative Oncology Group performance status was 1 (range, 0–2). The overall response rate was 36% [95% confidence interval (95% CI) = 18–54], with three complete responses and seven partial responses. The median time to progression was 6.2 months (95% CI = 3.9–8.5), and the median overall survival was 10.3 months (95% CI = 6.1–14.1). The most common Grade 3/4 nonhematologic and hematologic toxicities were emesis (10 of 28 patients; 36%) and neutropenia (5 of 110 cycles; 5%). CONCLUSIONS: Salvage chemotherapy with paclitaxel and cisplatin displayed promising results with tolerable toxicity profiles in patients with metastatic or locally advanced TCC who had been pretreated with G/C.